Glena bipennaria bipennaria and Apatelodes pandara (Lepidoptera): new defoliating insects associated with Khaya in Brazil - Luana de Souza Covre; Robert A. Haack; Carlos Alberto Hector Flechtmann (Pesquisa Florestal Brasileira)
The expansion of African mahogany (Khaya spp.) plantations in Brazil has led to an increase in the number of associated insect pests. Here we report the first instances of defoliating caterpillars [Glena bipennaria bipennaria (Guenée) (Geometridae) and Apatelodes pandara Druce (Apatelodidae)] on commercial stands of African mahogany in Brazil, specifically Khaya grandifoliola C. DC. and Khaya senegalensis (Desr.) A. Juss. Glena b. bipennaria was the dominant defoliator in all stands, with A. pandara only found in K. senegalensis stands. We provide data on seasonal development, defoliation severity, and natural enemies. It is currently unclear whether the Glena b. bipennaria outbreak reported is an isolated incident or will become more common in the future. Serious insect outbreaks, particularly those caused by defoliating caterpillars, only became frequent several decades after the introduction of Eucalyptus species to Brazil. African mahogany species were introduced much more recently, suggesting that additional native insects may adapt to these new exotic Khaya species in the coming years.